Linking the lytic and lysogenic bacteriophage cycles to environmental conditions, host physiology and their variability in coastal lagoons. (15th April 2013) - Maurice, C. F.; Bouvier, C.; de, R.; Bouvier, T.
Summary Changes in environmental conditions and prokaryote physiology can strongly affect the dynamics of both the lysogenic and lytic bacteriophage replication cycles in aquatic systems. However, it remains unclear whether it is the nature, amplitude or frequency of these changes that alter the phage replication cycles. We performed an annual survey of three Mediterranean lagoons with contrasting levels of chlorophyll a concentration and salinity to explore how these cues and their variability influence either replication cycle. The lytic cycle was always detected and showed seasonal patterns, whereas the lysogenic cycle was often undetected and highly variable. The lytic cycle was influenced by environmental and prokaryotic physiological cues, increasing with concentrations of dissolved organic carbon, chlorophyll a, and the proportion of respiring cells, and decreasing with the proportion of damaged cells. In contrast, lysogeny was not explained by the magnitude of any environmental or physiological parameter, but increased with the amplitude of change in prokaryote physiology. Our study suggests that both cycles are regulated by distinct factors: the lytic cycle is dependent on environmental parameters and host physiology, while lysogeny is dependent on the variability of prokaryote physiology. This could lead to the contrasting patterns observed between both cycles in aquatic systems.